Implementation of Home Telemedicine in Elderly with Dementia During the Covid-19 Pandemic: A Systematic Review - Tazia, M. Ali; Sriyono, Sriyono; Wahyudi, Andri Setya; Karingga, Devangga Darma (Indonesian Journal of Global Health Research, 2024)
Dementia is defined as a decrease in intellectual abilities which can cause changes in behavior, disruption in social life, and disruption in daily activities. Palliative care is a useful solution in the future to improve the quality of life for dementia sufferers during the COVID-19 pandemic. This systematic review aims to find out how the implementation of home telemedicine can become the main choice for elderly people with dementia during the COVID-19 pandemic. A database search was carried out by the PRISMA protocol focusing on Scopus, Proquest, Sage, ScienceDirect, and CINAHL identified based on MeSH-adjusted keywords, and A total of 2440 article journals were identified. Then deletion so that it remains 1086 article journals were reviewed. Then excluded (238) articles from journals based on 5 years, experimental test method with Randomized Controlled Trial design (RCT) and Experiments in language English, full text to be reviewed for feasibility so that 10 articles were obtained for review. From all articles, media innovation is very useful in implementing palliative care because of the various impacts of the global pandemic through the experiences of people with dementia and their care partners. The role of home-based palliative care using home telemedicine can potentially reduce the long-term impact of palliative care. The important role of palliative care integrated with long-distance services in informing health service priorities is to restore the quality of life and health of elderly people with dementia so that they are better prepared to face the future.